Prevalence and Clinical Profile of Common Sinonasal Disorders Among Children Attending Outpatient Clinics: A Cross-Sectional Study (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Sinonasal disorders are frequent in childhood, impacting quality of life and healthcare resources. However, data on their prevalence and clinical patterns in specific populations, particularly in post-conflict settings like Mosul, Iraq, are limited. Understanding the local burden is crucial for planning services and interventions. This study aimed to determine the prevalence of common sinonasal disorders (allergic rhinitis [AR], non-allergic rhinitis [NAR], acute bacterial rhinosinusitis [ABRS] based on clinical criteria, chronic rhinosinusitis [CRS], symptomatic adenoid hypertrophy [AH]) and identify associated factors among children attending outpatient clinics in Mosul.A cross-sectional study was conducted between September 1, 2022, and December 31, 2023, at pediatric and ENT outpatient clinics of Ibn Sina Teaching Hospital and Al-Khansaa Teaching Hospital in Mosul. Children aged 2 to 14 years presenting for any reason were screened. Caregivers completed a structured questionnaire covering demographics, sinonasal symptoms (using adapted criteria), duration, previous treatments, family history of atopy, and environmental exposures (e.g., household smoking). Prevalence rates were calculated, and associations were explored using chi-square tests and logistic regression.A total of 452 children were enrolled (mean age 7.1 ± 3.5 years; 54.0% male). The overall prevalence of any physician-diagnosed sinonasal disorder was 38.3% (n=173). The most prevalent conditions were AR (15.9%), symptomatic AH (12.6%), and clinically suspected ABRS (8.2%). Only 45% of children diagnosed with AR reported consistent use of intranasal corticosteroids when prescribed previously.Sinonasal disorders represent a significant health burden among children attending major outpatient clinics in Mosul, with allergic rhinitis and symptomatic adenoid hypertrophy being particularly common. Factors like family history of atopy and environmental smoke exposure are associated with specific conditions.